2016
DOI: 10.1002/tie.21846
|View full text |Cite
|
Sign up to set email alerts
|

Do All Emerging-Market Firms Partner with Their Acquisitions in Advanced Economies? A Comparative Study of 25 Emerging Multinationals’ Acquisitions in France

Abstract: Emerging multinationals' acquisitions in advanced economies are a growing phenomenon that remains relatively unexplored. Although there is now a consistent body of knowledge concerning multinationals from major emerging countries such as China, empirical data encompassing a larger array of countries of origin are still lacking. This article contributes to a better, contextualized understanding of commonalities and differences among emerging multinationals in terms of how they manage their developed-region-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 55 publications
1
46
0
Order By: Relevance
“…The limited number of studies touching upon integration issues in EMNEs has acknowledged that EMNE HQs have a low level of integration with their subsidiaries (e.g., Kale, Singh, & Raman, ;Liu & Woywode, ; Marchand, ). To go into more detail, in analyzing 120 deals for controlling stakes in Asian cross‐border M&As, Cogman and Tan () indicate that more than 43% of Asian deals involve either limited functional integration or no integration efforts whatsoever.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited number of studies touching upon integration issues in EMNEs has acknowledged that EMNE HQs have a low level of integration with their subsidiaries (e.g., Kale, Singh, & Raman, ;Liu & Woywode, ; Marchand, ). To go into more detail, in analyzing 120 deals for controlling stakes in Asian cross‐border M&As, Cogman and Tan () indicate that more than 43% of Asian deals involve either limited functional integration or no integration efforts whatsoever.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In addition, Liu and Woywode () identify that Chinese HQs employ a “light‐touch” approach which essentially synthesizes the preservation and symbiosis integration when managing acquired subsidiaries in Germany. From these limited studies, the antecedents of EMNEs' low level of integration are mainly summarized as: complicated institutional systems (Muralidharan, Wei, & Liu, ); administrative heritage (Marchand, ); cultural influences (Liu & Woywode, ; Weber, Tarba, & Reichel, ); insufficient M&A experience and lower absorptive capabilities (Liu & Woywode, ; Marchand, ); or organizational identity divergence (Wei & Clegg, ). However, the fragmented research fails to identify the fundamental reasons that explain this phenomenon.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The fact that Motherson opened its first overseas office in Austria is an indication of its international orientation. Both firms seem to have adopted the “light touch” integration approach (Kale & Singh, ; Kale, Singh, & Raman, ; Kumar, ; Liu & Woywode, ; Marchand, ) toward their developed‐region acquisitions. This is evident from our analysis that shows the two firms have retained the TMT at acquired entities.…”
Section: International Orientation Of Motherson and Rainmentioning
confidence: 99%
“…Emerging market multinationals (EMMs) have received increasing attention in international business literature in the last two decades (Agnihotri & Bhattacharya, 2018;Buckley et al, 2014;Demirbag et al, 2009;Marchand, 2017;Luo, 1998;Panibratov et al, 2018;Sarapovas et al, 2016). Studies have shown that EMMs differ from developed market multinationals (DMMs) in a number of areas such as strategic flexibility (Luo & Rui, 2009), motivation for expansion (Luo & Tung, 2007), pace of internationalization (Dunning, 2006;Mathews, 2006), and firm specific advantages (Guillen & Garcia-Canal, 2009).…”
Section: Introductionmentioning
confidence: 99%